2020
DOI: 10.1097/md.0000000000022764
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among patients with autoimmune hepatitis in remission

Abstract: Health-related quality of life (HRQOL) is lower in individuals with autoimmune hepatitis (AIH) than in the general population. However, previous evaluations of HRQOL for AIH have included a broad range of disease activities. The aim of this study was to clarify HRQOL among patients with AIH in remission. We assessed HRQOL in patients with AIH in remission, patients with chronic hepatitis C (CHC) with eradicated hepatitis C virus (HCV) and patients with primary biliary cholangitis (PBC) using the Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In the present study, no significant relationship was reported between alcohol, smoking and drug use and quality of life, similar to the results of other studies [33,34]. Takahashi et al [35] showed a relationship between alcohol consumption and reduced quality of life in patients with hepatitis C. Patients in that study not only suffered chronic alcoholism but also experienced social problems such as unemployment and family breakdown. The lack of significant difference might be due to the fact that most patients in these studies had previously stopped taking drugs for a long time.…”
Section: Resultssupporting
confidence: 91%
“…In the present study, no significant relationship was reported between alcohol, smoking and drug use and quality of life, similar to the results of other studies [33,34]. Takahashi et al [35] showed a relationship between alcohol consumption and reduced quality of life in patients with hepatitis C. Patients in that study not only suffered chronic alcoholism but also experienced social problems such as unemployment and family breakdown. The lack of significant difference might be due to the fact that most patients in these studies had previously stopped taking drugs for a long time.…”
Section: Resultssupporting
confidence: 91%
“…Despite this progress, a clear need still exists for better treatment options and expanded endpoints in every aspect of autoimmune hepatitis 71. First line and second line treatments are characterized by several mostly dosage dependent side effects that may greatly affect quality of life, even when biochemical and histological remission are reached 7273. This has a particular impact on children and adolescents, whose adherence to treatment is often lower 49.…”
Section: Quality Of Lifementioning
confidence: 99%
“…In Japan, it was also reported that patients with AIH had an impaired health-related QOL and that doctors should be aware of the risk when prescribing steroids ( 17 ). In addition, Takahashi et al demonstrated that even patients with AIH in remission showed an impaired health-related QOL associated with disease duration ( 18 ).…”
Section: Introductionmentioning
confidence: 99%